A better understanding of how gamification can help improve digital lifestyles - Wong, Chee Ken *; Lee, Chien Sing * (2016)
There are many people without or have little programming knowledge who have many creative ideas but do not have a platform to share, discuss, co-design and showcase their creative ideas. Therefore, in this capstone project, we aim to create a gamify Website to serve as a platform for different users to interact, engage and showcase their creativity. Significance of the study are first, there have been several studies on gamification in ecommerce and e-learning literature but our study is in the Malaysian context, focused on the effects of gamification to learning Science, Technology, Mathematics and Engineering (STEM), through a gamification website. Also, by creating a community of potential designers/creators, to increase interest in the learning of STEM (technology).